Pleural and Pericardiac Effusion as a Complication of Properly Placed Umbilical Venous Catheter - Unal, Sezin; Arifoglu, İlter and Çelik, İstemi Han and Yılmaz, Osman and Bas, Ahmet Yagmur and Demirel, Nihal (Journal of Neonatal Surgery, 2017)
Pleural and pericardial effusions are extremely rare complications of umbilical venous catheterization in newborns. A preterm male infant weighing 850g, with insertion of an umbilical venous catheter (UVC) developed massive right pleural and pericardial effusions. The position of catheter tip was verified by chest radiography and echocardiography. The effusions were drained by thoracentesis and pericardiocentesis without complication, and were biochemically similar as total parenteral infusion which infused through catheter.